Unraveling the impact of CO2 exhaust gas recirculation on flame characteristics and NOx emissions of premixed NH3/DME swirl flames - Tianyou Lian; Xiaoxiang Shi; Sibo Han; Yi Zhang; Zundi Liu; Zhongya Xi; Wei Li; Yuyang Li (Applications in Energy and Combustion Science, 2024)
The low combustion intensity and high NOx emissions of ammonia (NH3) pose challenges to its applications in energy and power devices. Co-firing strategies with reactive fuels, such as hydrogen, methane, syngas, and dimethyl ether (DME), have been proposed to enhance the combustion stability of NH3 in gas turbine, while exhaust gas recirculation (EGR) has the potential to reduce NOx emissions of combustion systems. This work explores the impact of CO2 EGR on the flame characteristics and NOx emissions of premixed NH3/DME swirl flames. CO2 EGR is observed to have a profound impact on both flame morphology and chemiluminescence intensity. With increasing CO2 EGR rate, which is described by the CO2 content in the oxidizer (χCO2), the chemiluminescence intensity becomes much weaker, the flame height rises, and the lean blowout (LBO) limit grows, indicating a reduced flame stability. Moreover, CO2 EGR affects the distribution of OH radical and weakens the OH fluorescence intensity. These impacts on flame characteristics mean that practical energy and power devices should be better designed to stabilize the flame. To unravel the underlying mechanism, kinetic analysis on premixed NH3/DME/air flame under non-EGR and CO2 EGR conditions is performed. Simulation results show that CO2 EGR substantially reduces the laminar burning velocity, maximum OH mole fraction, and NO mole fraction. The reduction of NO mole fraction is mainly attributed to the thermal effect of CO2 EGR. The chemical effect plays a positive role in reducing NO formation under lean conditions but enhances NO formation under rich conditions.